Implementation of a Public Speaking Program to Enhance Self-Confidence and Presentation Skills - Lydiawati Soelaiman; Jolin Jolin; Marissa Leviani (Journal of Innovation and Community Engagement, 2026)
Public speaking is one of the essential skills that young people need to develop, particularly to enhance soft skills such as self-confidence and effective communication. Many students still experience fear and anxiety when speaking in public, which often leads to passive participation in classroom learning. In response to this issue, this community service activity aimed to improve students' public speaking abilities through practice-based training. The program was conducted at Tarsisius I Junior High School in Jakarta and involved 8th and 9th-grade students. The implementation method included the delivery of material through interactive presentations using PowerPoint, followed by practical public speaking exercises in front of an audience. The program was evaluated through direct observation and the distribution of questionnaires to participants. The results showed that the majority of participants found the training to be both engaging and valuable. This activity demonstrates that public speaking training can serve as a strategic effort to enhance the quality of human resources and foster personal development among students.